Pengenalan Software Autodesk Inventor Untuk Meningkatkan Kompetensi Pelajar SMK di Kabupaten Gresik - Rilo Chandra Muhamadin; Alviani Hesthi Permata Ningtyas; Ilham Arifin Pahlawan; Rizkyansyah Alif Hidayatullah; Agin Viakri Dagmar; Purwo Sudirdjo; Bagus Hidayat; Rengga Wijaya (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Implementing the use of Autodesk Inventor software in technical drawing learning for vocational learners can significantly improve their competence. By learning this software, learners can develop the skills necessary to produce accurate and detailed technical drawings. From the Inventor software training that has been carried out to students of SMK Nurul Islam and SMK Muhammadiyah 1 Gresik, students have understood and increased their knowledge of Inventor software from 30% of students who have never tried this software before. Pelathan is conducted by lectures, questions and answers, demonstrations and exercises. The results of this Inventor software training received a 50% satisfaction assessment for the speakers, facilitators, and facilities obtained. As for the material provided by 63% with a good rating scale. Suggestions from participants during the training that training like this is often held to increase the competence of SMK students in Gresik.